Men in black 3 [videorecording (DVD)] - Sonnenfeld, Barry; Smith, Will, 1968-; Jones, Tommy Lee, 1946-; Brolin, Josh; Thompson, Emma; Elfman, Danny; Cunningham, Lowell, 1959- (Columbia Pictures, 2012)
Agent J must travel back in time to MIB's early years in the 1960s and save his partner, Agent K, from being assassinated by an alien. Along the way, Agent J teams up with young Agent K and learns that there are secrets to the universe that Agent K never told him.